PSYCHO-PHYSIOLOGICAL MANIFESTATIONS OF POSTTRAUMATIC STRESS AS REACTIONS TO ENSURE THE WHOLENESS OF PERSONALITY - MKRTUMYAN, MELS; SARGSYAN, LILIT (Main Issues Of Pedagogy And Psychology, 2015)
The article discusses the setting of the stress, posttraumatic stress disorder issue, the characteristics of psycho-physiological manifestations, personality characteristics and the typical stages oftheir impact on the body. It reveals the psychological analysis ofthe main characteristics for the prevention and it is suggested the ways and resources of psychological support of posttraumatic stress.